2005
DOI: 10.1200/jco.2005.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Outcome of Human Herpesvirus 8–Associated Primary Effusion Lymphoma in Patients With AIDS

Abstract: Based on a retrospective series of 28 patients, two prognostic factors were identified as being independently associated with impaired clinical outcome in HIV-related PEL--(1) a poor performance status and (2) the absence of HAART before PEL diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
237
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 287 publications
(251 citation statements)
references
References 32 publications
9
237
4
1
Order By: Relevance
“…In addition, some case reports have documented long-term survival with HAART alone (15,16). The most recent multicenter series of 28 patients showed a median survival time of 6.2 months and 1-year overall survival of 39.3%, which is similar to results from small patient series (17). In that multicenter study, Boulanger et al concluded that the only two negative prognostic factors in HIV-related PEL were poor performance status and absence of HAART prior to PEL diagnosis.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, some case reports have documented long-term survival with HAART alone (15,16). The most recent multicenter series of 28 patients showed a median survival time of 6.2 months and 1-year overall survival of 39.3%, which is similar to results from small patient series (17). In that multicenter study, Boulanger et al concluded that the only two negative prognostic factors in HIV-related PEL were poor performance status and absence of HAART prior to PEL diagnosis.…”
Section: Discussionsupporting
confidence: 68%
“…Lactate dehydrogenase concentration is, in general, elevated [27]. Bone-marrow biopsy may show haemophagocytosis but rarely tumour cells [24,27].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Pleural effusion is present in 85% of cases and is associated with ascites in 50% of cases [24]. PEL may also be revealed by a cardiac tamponade secondary to a specific pericardial localisation [27].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations